2013
DOI: 10.1186/1477-5956-11-34
|View full text |Cite
|
Sign up to set email alerts
|

A note on protein expression changes in chicken breast muscle in response to time in transit before slaughtering

Abstract: Aims of the research were to devise a proteome map of the chicken Pectoralis superficialis muscle, as resolved by two-dimensional gel electrophoresis, and to characterize protein expression changes in the soluble protein fraction in commercial conditions due to age and to time in transit before slaughtering. Broilers were reared under commercial conditions until they reached a mean 1.8 kg and 36 d, or 2.6 kg and 46 d of age. Transport to the slaughterhouse took 90 or 220 minutes. Transport-induced stress was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Notably these were expressed by bands corresponding to the Enolase, pyruvate kinase (PK), and the glyceride phosphate dehydrogenase (GAP). This confirms the studies of Zanetti et al (2013) who reported an increased expression of five proteins involved in the energy metabolism among these were phosphoglycerate kinase, and beta-enolase.…”
Section: Discussionsupporting
confidence: 90%
“…Notably these were expressed by bands corresponding to the Enolase, pyruvate kinase (PK), and the glyceride phosphate dehydrogenase (GAP). This confirms the studies of Zanetti et al (2013) who reported an increased expression of five proteins involved in the energy metabolism among these were phosphoglycerate kinase, and beta-enolase.…”
Section: Discussionsupporting
confidence: 90%
“…Another important food consumed for body formation is chicken breast where consumption of chicken breast accelerates the growth of muscle cells. However, stress conditions will also affect the body's metabolism and accelerated muscle growth [17,18,20].…”
Section: Resultsmentioning
confidence: 99%
“…Other possibilities may that the probiotic activity of the filamentous fungus Monascus purpureus used as fermentation starter effected on the protein digestibility and thus enhance the protein availability for haematopoietic activity. Note that protein is a crucial nutrient needed for red blood cells as well as haemoglobin synthesis (Zanetti et al, 2013).…”
Section: Biochemical Parametersmentioning
confidence: 99%